2012
DOI: 10.4103/0019-557x.96955
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence among ever married women of reproductive age group in a slum area of Kolkata

Abstract: Overall prevalence of domestic violence was 54%, of which 41.9% suffered from both current and lifetime physical and psychological violence. Presence of property, higher per capita income and social support were protective factors against domestic violence, whereas alcohol addiction and multiple sex partners were the important contributory factors for it. The study recommended more social support, awareness and income generation for women in the slum areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
72
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 2 publications
16
72
5
3
Order By: Relevance
“…This is almost similar to the findings of many studies with 54%,36.9%% women reporting domestic violence in India. [6,7] On comparing the prevalence of different forms of domestic violence in our findings to many population based studies, the prevalence of physical violence was found to be the same, i.e. around 14-34% in other studies, [7,8] while that of emotional violence was found tobe higher than other studies.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…This is almost similar to the findings of many studies with 54%,36.9%% women reporting domestic violence in India. [6,7] On comparing the prevalence of different forms of domestic violence in our findings to many population based studies, the prevalence of physical violence was found to be the same, i.e. around 14-34% in other studies, [7,8] while that of emotional violence was found tobe higher than other studies.…”
Section: Discussioncontrasting
confidence: 38%
“…Evidence from other studies supported husbands alcohol consumption as a significant factor of domestic violence [6]and might be because of reduced selfcontrol of individuals due to excessive alcohol consumption. Working women were found more likely to experience violence than women who were not working in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A Study by Borah showed domestic violence in 26.4% of study participants and further, of all types psychological violence was most common. 20 More severe forms physical violence like burns, dislocation, cuts were found to be rare (1.75%) in our study. In NFHS-3, among evermarried women it was found that 12% of women reported to have been kicked, dragged, or beaten up, and 2% reported that their husbands tried to choke or burn them on purpose.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have reported about the prevalence of IPV among women with low socio-economic and demographic profiles such as urban residence, lower education, and lower family income. 6,13,[22][23][24][25][26][27] The majority of them were housewives and financially dependent upon husbands which put them under the risk of violence. In-laws' interferences, decision-making process by husband and other family members and less time spent with each were factors contributed to DV.…”
Section: Discussionmentioning
confidence: 99%